2013
DOI: 10.1111/2049-632x.12064
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the host protein interactors ofChandipura virususing a structural similarity-based approach

Abstract: Chandipura virus (CHPV), alike other pathogens, exploits the cellular infrastructure of their hosts through complex network of interactions for successful infection. CHPV being a recently emerged pediatric encephalitic virus, the mechanisms involved in the establishment of viral persistence are still ill defined. Because the protein interface between CHPV and its host provides one means by which the virus invades and seize control of their human host machinery, the authors in this study have employed computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Moreover, for VSV as well as for hepatitis C virus (6567), mouse hepatitis coronavirus (68), chikungunya virus (69), poliovirus (57, 58, 70), coxsackievirus (71) and classical swine fever virus (72), COPI/Arf1 has been shown to be necessary for genome replication as well as for viral protein expression. COPI/Arf1 has also been shown to be critical for viral particle assembly of influenza and the Chandipura virus (62, 73). The specific mechanism through which COPI/Arf1 participate in these processes has not been characterized; however, GBF1, involved in the first step of the COPI/Arf1 transport process, has been shown to play an important role for the replication of some of these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for VSV as well as for hepatitis C virus (6567), mouse hepatitis coronavirus (68), chikungunya virus (69), poliovirus (57, 58, 70), coxsackievirus (71) and classical swine fever virus (72), COPI/Arf1 has been shown to be necessary for genome replication as well as for viral protein expression. COPI/Arf1 has also been shown to be critical for viral particle assembly of influenza and the Chandipura virus (62, 73). The specific mechanism through which COPI/Arf1 participate in these processes has not been characterized; however, GBF1, involved in the first step of the COPI/Arf1 transport process, has been shown to play an important role for the replication of some of these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for VSV as well as for hepatitis C virus (66)(67)(68), mouse hepatitis coronavirus (69), chikungunya virus (70), poliovirus (58,59,71), coxsackievirus (72), and classical swine fever virus (73), COPI/Arf1 has been shown to be necessary for genome replication as well as for viral protein expression. COPI/Arf1 has also been shown to be critical for viral particle assembly of influenza virus and the Chandipura virus (63,74). The specific mechanism through which COPI and Arf1 participate in these processes has not been characterized; however, GBF1, involved in the first step of the COPI/Arf1 transport process, has been shown to play an important role for the replication of some of these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a structure-based computational analysis of possible protein–protein interactions between human proteins and the proteins of Chandipura virus (CHPV), another member of the Vesiculovirus genus, which has emerged as a pediatric encephalitic virus in India [ 127 , 128 ], revealed that GBF1 and Arf1 exhibit a high potential for interaction with the G and L proteins of this virus [ 129 ]. Although the association of GBF1 and Arf1 with the G protein was rather expected, given the association of the G protein with the secretory pathway, the potential interaction of GBF1 and Arf1 with the polymerase L of CHPV is a surprising finding that might indicate that GBF1 could directly regulate the activity of the L protein during viral RNA replication; the interaction between GBF1 and the L protein was not corroborated by biochemical assays.…”
Section: Negative-sense Rna Virusesmentioning
confidence: 99%